Role of Climate Change in Afghanistan’s Geopolitical Power - YAR, Fayaz Gul Mazloum; ZAHID, Shamsurahman; MIAKHIL, Jan Mohammad (Indonesia Strategic Sustainability, 2024)
Purpose: This study examines the role of climate change in Afghanistan’s geopolitical power. Global warming and climate change are the most significant environmental threats today. The effects of climate change include water and food scarcity, disease, unemployment, migration, poverty, resource conflicts, and global instability.Methodology:This study examines the role of climate change in Afghanistan's geopolitical power. This study employs a descriptive-analytical approach and a survey method. The statistical research community includes experts and specialists in geopolitics, political science, climate science, and university professors. The questionnaire was distributed among them based on climate change, development, and geopolitics indicators. 80 questionnaires were collected.Findings: Based on these findings, a significant and inverse relationship exists between climate change's impacts and development. Furthermore, reducing the development process significantly and negatively impacts Afghanistan's geopolitical power. Finally, reducing development affects change. Climate plays a mediating role in geopolitics. Then, the priority of parameters influencing climate change in geopolitics was discussed using Friedman's comparison test.Implication:These parameters include 1) poverty, social anomalies, drought, and migration. In the suggestions section, effective methods, such as irrigation and the use of clean energy, must be implemented to reduce greenhouse gas emissions and adapt to the impacts of climate change.